Condensed droplet-based electricity generation via water-phase change. (April 2021) - Shin, Gunsub; Yong, Hyungseok; Chung, Jihoon; Cho, Eunho; Ju, Jihong; Lin, Zong-Hong; Kim, Dongseob; Lee, Hyungsoon; Koo, Bonwook; Lee, Sangmin
Abstract: Water electrification mechanism is gradually being identified, and utilized to harvest various types of water-based energy. However, a lack of understanding of the complementary characteristics of water in real environment, such as the complex dynamics of droplet flow, phase change, high temperature, and humid conditions, continues to limit the realization of water-based energy harvesting. Here, we demonstrated the mechanism of condensed droplet-based electricity generation via water-phase change for the first time. The various characteristic electrical outputs were observed in a series of condensation processes (nucleation, growth, shedding, sweeping, separation, drop off). Furthermore, the correlation among the electrical outputs, heat flux, and condensation rate were identified. The distinct changes in the electrical outputs depending on changes in the heat flux changes can be utilized to detect sudden failures of heat exchanges and coolers. Graphical Abstract: ga1 Highlights: This study clarified the electricity generation mechanism of condensed droplet. Correlation between electrical outputs and heat exchange of water was identified. CDEG can detect sudden failures of heat exchangers and coolers.